Unleashing the Power of Self-Esteem: Focus on Emotional Intelligence and Self–Efficacy - Sangeetha, D.; Latha Natarajan, M. (Prabandhan: Indian Journal of Management, 2019)
Good teaching requires emotional power more than brain power. It is one of the powerful elements of personality that was not recognized by many of the teaching professionals over the years. Researchers have found that emotional quotient is more important than the intelligence quotient in one's day-to-day work performance and achievements. It contributes to the performance of work duties and improves the attitude of a person as well as also improves the self confidence in one's state of mind. Therefore, this study aimed to combine the psychological factor of Emotional Intelligence along with Teaching Efficacy in order to determine the Self-Esteem of teaching professionals working in various colleges. The method used in the study was descriptive method. Primary data were collected using an online survey from teaching professionals from all Engineering, Arts and Science, Polytechnic, and Bachelor of Education colleges in India. In this study, statistical tools like structured equation modeling, MANOVA, ANOVA, correlation and regression analysis, factor analysis, and discriminant analysis were used. From the analysis made on the impact of demographic factors on attitude measures like Emotional Intelligence, Teaching Efficacy, and Self Esteem, it was found that the socioeconomic factor: gender had a significant impact on the attitude measures. The results also revealed that there was a positive and significant combined effect of Emotional Intelligence measures and Teaching Efficacy measures in determining and enhancing the self-esteem of teaching professionals.